2005
DOI: 10.1128/iai.73.8.5217-5221.2005
|View full text |Cite
|
Sign up to set email alerts
|

Selective Capture ofSalmonella entericaSerovar Typhi Genes Expressed in Macrophages That Are Absent from theSalmonella entericaSerovar Typhimurium Genome

Abstract: Thirty-six Salmonella enterica serovar Typhi-specific genes, absent from the Salmonella enterica serovar Typhimurium genome, that were expressed in human macrophages were identified by selective capture of transcribed sequences. These genes are located on 15 unique loci of the serovar Typhi genome, including Salmonella pathogenicity islands (SPI-7, SPI-8, and SPI-10) and bacteriophages (ST15, ST18, and ST35).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
22
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 33 publications
2
22
0
Order By: Relevance
“…In typhoid fever patients, antibodies to three fimbrial systems, Tcf, Stb, and Csg, were detected (10). Nevertheless, we have previously detected the stgCЈ transcript during infection of macrophages (6). The optimal conditions for expression of Stg may not have been found yet, and we need to further investigate its regulation, but our results are consistent with the hypothesis that the stg fimbrial operon may be important for the initial interaction with host cells.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…In typhoid fever patients, antibodies to three fimbrial systems, Tcf, Stb, and Csg, were detected (10). Nevertheless, we have previously detected the stgCЈ transcript during infection of macrophages (6). The optimal conditions for expression of Stg may not have been found yet, and we need to further investigate its regulation, but our results are consistent with the hypothesis that the stg fimbrial operon may be important for the initial interaction with host cells.…”
Section: Discussionsupporting
confidence: 78%
“…Serovar Typhi is restricted to humans and harbors 13 putative fimbrial systems and a type IV pilus (29). We have previously found that stg is transcribed by serovar Typhi within macrophages (6). In S. enterica, the stg fimbrial cluster located in the glmS-pstS region is present only in serovar Typhi (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is of interest to investigate the signals or conditions that activate this genetic system. For S. Typhi, the selective capture of genes expressed in macrophages showed that the third component of the CRISPR/Cas system, STY3068 (casC ortholog), is induced under these conditions (17), and according to Deiwick et al (15), a minimal medium deficient in magnesium and phosphate simulates the environmental niche encountered by Salmonella in the eukaryotic cell, since several genes of Salmonella pathogenicity island 2 that are relevant to the survival of this pathogen inside macrophages are induced in this medium (10).…”
Section: Vol 193 2011mentioning
confidence: 99%
“…To overcome these problems, the selective capture of transcribed sequences (SCOTS) was developed to identify bacterial genes expressed during infection (20). This technique has been successfully used with many pathogens, such as Mycobacterium, Salmonella, Actinobacillus, Helicobacter, and Streptococcus (4,8,12,15,21,27). SCOTS was recently used in combination with a DNA microarray in order to provide an effective way to elucidate the global bacterial expression profile, or transcriptome, from infected host cells (13).…”
mentioning
confidence: 99%